Neural correlates of trait anxiety in fear extinction - Sehlmeyer, C.; Dannlowski, U.; Schöning, S.; Kugel, H.; Pyka, M.; Pfleiderer, B.; Zwitserlood, P.; Schiffbauer, H.; Heindel, W.; Arolt, V.; Konrad, C. (Psychological medicine, 2011)
Fear conditioning involves the amygdala as the main neural structure for learning fear responses whereas fear extinction mainly activates the inhibitory prefrontal cortex (PFC). In this study we investigated whether individual differences in trait anxiety affect amygdala and dorsal anterior cingulate cortex (dACC) activation during fear conditioning and extinction. Thirty-two healthy subjects were investigated by functional magnetic resonance imaging (fMRI) at 3 T while performing a cued fear-conditioning task. All participants completed the trait version of the State-Trait Anxiety Inventory (STAI-T). Activations of the amygdala and the dACC were examined with respect to the effects of trait anxiety. Analysis of the fMRI data demonstrated enhanced activation in fear-related brain areas, such as the insula and the ACC, during both fear conditioning and extinction. Activation of the amygdala appeared only during the late acquisition phase whereas deactivation was observed during extinction. Regression analyses revealed that highly trait-anxious subjects exhibited sustained amygdala activation and reduced dACC involvement during the extinction of conditioned responses. This study reveals that high levels of trait anxiety are associated with both increased amygdala activation and reduced dACC recruitment during the extinction of conditioned fear. This hyper-responsivity of the amygdala and the deficient cognitive control during the extinction of conditioned fear in anxious subjects reflect an increased resistance to extinct fear responses and may thereby enhance the vulnerability to developing anxiety disorders.